2005
DOI: 10.1001/archpsyc.62.10.1129
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Deficits in Adults With Attention-Deficit/Hyperactivity Disorder

Abstract: Disturbed attentional processing of the stop signal contributed to impaired stopping in adults with ADHD. This finding may have implications for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 49 publications
9
72
4
1
Order By: Relevance
“…Moreover, the P3 is altered in clinical groups such as those with schizophrenia and ADHD (Bekker et al, 2005;Groom et al, 2008;Groom et al, 2010;Hughes, Fulham, Johnston, & Michie, 2012;Wiersema & Roeyers, 2009) and the NGA described by Fallgatter et al is also reduced in these groups (Fallgatter, 2001;Fallgatter et al, 2004;Fallgatter & Muller, 2001). …”
Section: The P3 Event-related Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the P3 is altered in clinical groups such as those with schizophrenia and ADHD (Bekker et al, 2005;Groom et al, 2008;Groom et al, 2010;Hughes, Fulham, Johnston, & Michie, 2012;Wiersema & Roeyers, 2009) and the NGA described by Fallgatter et al is also reduced in these groups (Fallgatter, 2001;Fallgatter et al, 2004;Fallgatter & Muller, 2001). …”
Section: The P3 Event-related Potentialmentioning
confidence: 99%
“…In particular, reduced N2 amplitude has often been hailed as a marker of impaired inhibitory control in ADHD (Barry et al, 2003;Brandeis et al, 1998;Groom et al, 2010;Liotti et al, 2005). However, this population also tend to show reduced P3 amplitude (Bekker et al, 2005;Groom et al, 2008;Groom et al, 2010;Hughes et al, 2012;Wiersema & Roeyers, 2009) and altered P3 topography (Fallgatter et al, 2004) as well as a much wider range of deficits in action control (Johnson et al, 2007;Kuntsi & Klein, 2012;Simmonds et al, 2007). Establishing the parameters that modulate the N2 and P3 will improve the measurement of action control in ADHD and other clinical populations, potentially leading to a more refined understanding of the particular neural systems that underlie in specific disorders or symptom dimensions.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…The no-go N2-P3 complex is consistently seen over fronto-central scalp sites on trials requiring response inhibition, 200-600 msec after no-go stimulus onset. Although their functions are debated, there is consensus that the N2 component probably indexes aspects of response selection or conflict detection that signal the need for response inhibition (Falkenstein, 2006;Kok, Ramautar, De Ruiter, Band, & Ridderinkhof, 2004) while the latency and amplitude of the P3 have been shown to predict successful inhibitions in keeping with Logan's (1994) race model of inhibition (Bekker, Overtoom, et al, 2005;Bekker, Kenemans, & Verbaten, 2004;Falkenstein, Hoomann, & Hohnsbein, 1999). Hence, the findings of Dockree et al suggest a reduced requirement for response inhibition in the SART fixed .…”
Section: Introductionmentioning
confidence: 95%
“…The contribution of non-inhibitory processes is still largely neglected in the 'reactive' inhibitory control literature, even though computational work indicates that most of SSRT is occupied by afferent processes Logan et al, 2014Logan et al, , 2015Salinas & Stanford, . Other studies have shown that stopping deficits in certain clinical populations could be due to impairments in signal detection rather than in inhibition per se (e.g., Bekker et al, 2005). Thus, a failure to detect the signal quickly can have important consequences and lead to 'stopping' deficits.…”
Section: Cortical-basal Ganglia Modelmentioning
confidence: 99%